Potential of computer-supported collaborative learning application use in Malaysian schools - Kasirun, Z.M.; Salim, S.S. (2004)
Abstract: The evolution of courseware in schools with its various attributes, strengths and limitations are increasing. The situation in Malaysian context is not widely known. Particularly with the government effort in implementing the smart school project, the readiness among school teachers would play important role. This paper focuses on the evolution of courseware in schools in general and discusses its attributes, strengths and limitations. Then, the paper presents the details of the survey on collaborative learning carried out among school teachers. The important issues that will be investigated include. the awareness of CL activities, the awareness of using CSCL applications, the teachers involvement in CSCL application development, the CL main and CL success factors.